Pemanfaatan Rempah Pilihan Sebagai Jamu Imunitas di Masa New Normal - Nuril Huda (Universitas Muhammadiyah Semarang, 2022)
In this new normal era, besides complying with health protocols, it is also important to maintain good immunity. One of the efforts to maintain a healthy body is by consuming selected spices that are used as immunity herbs. This community service activity aims to socialize the efficacy and methods of immune herbs made from selected spices. The method used in community service is the community development method. The activity was carried out in Petungsewu Village, Dau District, Malang Regency on December 26, 2020, and involved 15 participants. The material was delivered using the lecture method, then continued with discussions and simulations of making immunity herbs. Interviews were also conducted to obtain participant responses. The results of the activity showed that the participants were enthusiastic about participating in the activity from beginning to end. Participants listened to material about the active compounds contained in selected spices consisting of turmeric, ginger, lemongrass, cinnamon, cloves, and lime, as well as their health benefits as antibacterial, antioxidant, anti-inflammatory, can warm the body, and so on. Participants also looked at the pamphlets that were distributed. Participants also gave a positive response when participating in the practice of making herbal medicine and be able to make immunity herbs independently.